2010
DOI: 10.1007/s11207-009-9497-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical Comment on the Article by R. Rek “The Maunder Minimum and the Sun as the Possible Source of Particles Creating Increased Abundance of the 14C Carbon Isotope”

Abstract: Several strong but erroneous statements were made by R. Rek in an article published in this volume of Solar Physics. Here we show that these misleading statements are caused by neglecting the known effects of the carbon cycle and misinterpretation of the data. In particular we show that the claim of the Maunder minimum being "the period without a significant cessation of activity" contradicts the bulk of observational evidence and is caused by the misinterpretation of proxy data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Hence, the AD 774/5 event (as solar flare) either was not beamed that strongly, and/or it would have been much more than 4-6 times stronger than Carrington, and/or the lower energy estimate ) is not correct, and/or such solar flares cannot form (enough) 14 C and 10 Be, and/or the Carrington event itself was much softer than the AD 774/5 event. A similar conclusion was previously drawn by Kocharov et al (1995), Stuiver et al (1998b), and Usoskin & Kovaltsov (2010).…”
Section: Solar Flaressupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, the AD 774/5 event (as solar flare) either was not beamed that strongly, and/or it would have been much more than 4-6 times stronger than Carrington, and/or the lower energy estimate ) is not correct, and/or such solar flares cannot form (enough) 14 C and 10 Be, and/or the Carrington event itself was much softer than the AD 774/5 event. A similar conclusion was previously drawn by Kocharov et al (1995), Stuiver et al (1998b), and Usoskin & Kovaltsov (2010).…”
Section: Solar Flaressupporting
confidence: 90%
“…too small (compared to the observed ratio of ≥ 270 ± 140, HN13). Masarik & Ready (1995) and Usoskin et al (2006) concluded that the effect of 14 C production due to solar particles is negligible (less than 1 % on average) for both with cascades and without cascades, confirmed again by Usoskin & Kovaltsov (2010). M12 excluded a solar flare partly based on the fact that such flares are not hard enough to explain the differential 14 C to 10 Be production ratio.…”
Section: Possible Causesmentioning
confidence: 81%